Who Will Govern the New World?the Present and Future of the G20. - Renmin University of China, Chongyang Institute for Financial Studies (Ibidem Press, 2016)
How can the G20 fulfill their role most efficiently in the post-crisis era, and what role do the emerging economies play in the new global economic order? This timely volume provides an overview of the most important challenges ahead for the G20, especially China.